Hubungan Antara Dukungan Sosial dengan Motivasi untuk Sembuh pada Pasien Kanker Payudara (Carcinoma Mammae) di RSI Sultan Agung Semarang - Dhita Agustina; Erna Melastuti; Indah Sri Wahyuningsih (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
The family has an important role in the treatment process of cancer patients, especially in providing motivation during treatment. Social support from families has a great influence on the psychological condition of breast cancer patients undergoing chemotherapy. As the health workers who interact most intensely with patients, nurses play a role in empowering families through education and counseling to improve the quality of support provided. This study aims to analyze the relationship between social support and motivation to recover in breast cancer patients at RSI Sultan Agung Semarang. The study used a correlational descriptive design with a cross-sectional approach. The sample consisted of 77 respondents who were selected using purposive sampling techniques based on certain inclusion criteria. Data collection was carried out through a structured questionnaire, and statistical analysis was carried out using the Pearson correlation test. The results showed a significant relationship between social support and motivation to recover, with a correlation value of 0.478 and a p-value of 0.000 (p < 0.05). These findings suggest that the higher the level of social support patients receive, the greater their motivation to recover. The conclusion of this study is that social support has a positive contribution to increasing the healing motivation of breast cancer patients. Therefore, nursing interventions that actively involve families need to be improved as part of a holistic approach to the care of cancer patients.